On Being Wholeheartedly Ambivalent: Indecisive Will, Unity of the Self, and Integration by Narration - Schramme, Thomas (Ethical theory and moral practice, 2014)
In this paper, I want to discuss the relation between ambivalence and the unity of the self. I will raise the question whether a person can be both ambivalent about his own will and nevertheless be wholehearted. Since Harry Frankfurt’s theory is my main point of reference, I briefly introduce his account of the will and the reasons for his opposition towards ambivalence in the first section. In the second section, I analyse different interpretations of ambivalence. In the third section, I provide a narrative account of a diachronic integration of the self that allows for the integration of volitional ambivalence. Finally, I scrutinise different meanings of the unity of the self, since disintegration, not ambivalence, seems to be bad for us. I conclude that persons can indeed be wholeheartedly ambivalent.